Manganese detection in marine sediments: anodic vs. cathodic stripping voltammetry. - Banks, C; Kruusma, J; Moore, R; Tomcík, P; Peters, J; Davis, J; Komorsky-Lovrić, S; Compton, R (2005)
Three different electroanalytical techniques for the detection of manganese in marine sediments are evaluated. The anodic stripping voltammetry of manganese at an in situ bismuth-film-modified boron-doped diamond electrode and cathodic stripping voltammetry at a carbon paste electrode are shown to lack the required sensitivity and reproducibility whereas cathodic stripping voltammetry at a bare boron-doped diamond electrode is shown to be reliable and selective with a limit of detection, from applying a 60s accumulation period of 7.4 x 10(-7)M and a sensitivity of 0.24AM(-1). The method was used to evaluate the manganese content of marine sediments taken from Sibenik, Croatia.